The Perils of Attention From Headquarters - Levy, Orly; Barsoux, Jean-Louis; Bouquet, Cyril (MIT Sloan Management Review, 2015)
Operations in growing markets such as China often draw substantial attention from corporate headquarters. Unfortunately, that attention does not always add value -- and can even impede performance.
Keywords: Industrial management; Gestion d'entreprise